Meningkatkan Hasil Belajar Pendidikan Agama Katolik (PAK) Dengan Model Problem Based Learning (PBL) Berbantu Media Powerpoint Pada Materi Saya Tumbuh dan Berkembang Bagi Siswa Fase B Kelas III SD - Asta Ulina (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Study aims to examine the enhancement of student motivation and affective aspects related to collaboration and critical thinking through the Problem-Based Learning (PBL) model at UPT SPF SDN 101864 GUNUNG RINTIH. The research is grounded in issues such as low motivation, limited student engagement due to large class sizes, and the need to improve social skills within the context of Catholic Religious Education (PAK) and Character Education. This research employs a classroom action research design, involving the steps of planning, implementation, observation, and reflection in each cycle. The study consists of two cycles conducted with third-grade students at UPT SPF SDN 101864 GUNUNG RINTIH focusing on PAK content. The research is carried out in September 2024. Data collection techniques include observation and rubrics for assessing student motivation and affective dimensions of collaboration and critical thinking. Data analysis utilizes descriptive qualitative techniques. Results from the first cycle indicates an improvement in student motivation and engagement, though the targets were not fully met. In the second cycle, there was a significant increase in both student motivation and affective dimensions. The research demonstrated a 35% increase in student motivation and engagement in PAK learning, suggesting that the PBL approach fosters a more active and collaborative learning environment. This study is expected to contribute to providing holistic and meaningful education for students, aligning with the objectives of the Merdeka Curriculum and the values outlined in the Pancasila Student Profile.